One-Week Effects of Antibiotic Treatment on Gut Microbiota of Late Neonates With Pneumonia or Meningitis - Han, Shujing; Zhang, Qiaoru; Ding, Yijun; Chu, Ping; Zhang, Jinjing; Shi, Jin; Jia, Shengnan; Yang, Caiyun; Lu, Jie; Wang, Yajuan (Frontiers in Pediatrics, 2021)
Background: The neonatal period is a critical period for the establishment of the intestinal microbial community. Antibiotics can change the composition of gut microbiota. Methods: Fecal samples were collected from 14 patients with pneumonia and 14 patients with meningitis before and after antibiotics treatment, and fecal samples from 5 healthy neonates at 14th, 21th days after birth were collected as well. DNA of fecal samples was extracted and PCR amplification was performed targeting V3-V4 variable region of 16S rDNA. After detection by high throughput sequencing, OTUs (Operational Taxonomic Units) clustering, species annotation, α diversity analysis were calculated and analyzed statistically. Results: In the healthy control group, the abundance of Bifidobacterium increased significantly from 16.75% to 40.42%, becoming the most dominant bacteria. The results of α diversity analysis suggested that the Sobs indexes of the gut microbiota in the pneumonia and meningitis groups were significantly lower than that in the healthy control group (P < 0.05). PCoA analysis showed that the gut microbiota of pneumonia and meningitis groups clustered distinctly with the control group. (Adonis p=0.001, R2=0.565). And there was no significant change in the diversity of gut microbiota before and after the use of antibiotics. Conclusions: The gut microbiota of neonates with infectious diseases were mainly related to the disease conditions. The initial state of neonatal gut microbiome determines its state after one-week antibiotic treatment. Antibiotic application with 7 days had little effect on the community richness and some effect on the composition of gut microbiota of neonates with pneumonia or meningitis.